O gradiente latitudinal influencia os padrões de redes de interação parasito-hospedeiro? - Carvalho, Elvis Franklin Fernandes de (2019)
Macroecological studies including the use of networks, help in understanding ecological patterns such as specialization and distribution of species across large geographic ranges. Investigating the influence of latitude on interactions between organisms such as parasite-host demonstrate how they interact throughout their distribution and may reveal the mechanisms underlying these associations, such as niche amplitude of the species. We constructed nine networks using interactions data between helminth parasites of lizards in order to investigate whether latitude exerts influence on the topology of networks, specialization and the distribution of interactions along the area of occurrence. We observed that regionally network was modular due to the antagonistic and specialist nature of the interactions. The distribution of hosts at the collection sites differed with respect to the parasites being more dispersed. With this, the parasites showed great apacity of dispersion, being able to infect hosts of different families given the phylogenetic closeness within the biological order (Squamata). The specific interactions were, for the most part, restricted to the collection site. This is due to the restricted occurrence of parasites and mainly of hosts whose showed low amplitude of dispersion in relation to their parasites. The dissimilarity of these interactions between the collection sites did not follow a standard, and for this we attribute abiotic influences characteristic of each site, such as the climate, that may interfere in the distribution of host species. Only two of the local networks presented a modular pattern, these were located in the lower latitudes of this study and we associate this result, since the specialization, strongly related to modularity, is stronger near the tropics.